Sustainable Hausa Design, Culture and Usability: A Reflection on selected Arts of Northern Nigeria - Ologunwa, Temitope Peter (Advances in Social Sciences Research Journal, 2014)
The Hausa states were collection of independent city states situated in what became Northern Nigeria. The leadership of the Sokoto caliphate by Usman Dan Fodio led to conquering of the other Hausa states thereby creating a united centralized state with united set of people under the Muslim Fulani Empire. The Northern Nigeria was a British colony from 1900 as a result of 1885 Treaty of Berlin which broadly granted Northern Nigeria to Britain on the basis of their protectorate in Southern Nigeria. The Islamic influence in all the sphere of life of the majority of the people from Northern Nigeria have greatly influence their socio-economic activities with emphasis on how art, design and culture have interplay effectively. The need arose to evaluate the participatory developmental use of design that is broadly recognized and acceptable as universal visual and culture-oriented business conducted across all disciplines from multi-dimensional and multi-directional characters. This paper closely studied the design application from the Northern part of Nigeria with emphasis on culture and Development thesis generating such questions as: does certain cultural trait promote economic development, does economic development still exist in certain cultural trait and finally if culture and economic development anchored on design concepts are relatively autonomous. Conclusively responsibility of design symbols in the context of visual image producers as well as today market economy in cultural industries such as printing, multi-media, audio-visual, architecture, visual and perform art, sport, musical instruments advertising and cultural tourism were appraised. Keywords: Design, Symbols, Culture, Creative industries and Sustainable economy development.